2017
DOI: 10.1007/s11481-017-9774-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Early Postnatal Microglial Colonization of the Developing Rat Hippocampus Following a Single-Day Alcohol Exposure

Abstract: Microglia are involved in various homeostatic processes in the brain, including phagocytosis, apoptosis, and synaptic pruning. Sex differences in microglia colonization of the developing brain have been reported, but have not been established following alcohol insult. Developmental alcohol exposure represents a neuroimmune challenge that may contribute to cognitive dysfunction prevalent in humans with Fetal Alcohol Spectrum Disorders (FASD) and in rodent models of FASD. Most studies have investigated neuroimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 67 publications
(89 reference statements)
1
24
0
Order By: Relevance
“…The examination of both male and female fetal brains and placentas allowed us to investigate sex differences in response to immune challenge in the setting of maternal obesity. The finding that male brain and placental macrophages have a significantly increased response to LPS in maternal obesity is consistent with other studies that have demonstrated increased male brain vulnerability to early‐life immune challenge (Schwarz et al, 2012; Iwasa et al 2010; Llorente et al 2009; Rebuli et al 2016; Ruggiero et al 2018; Hilton et al, 2003; Nunez et al, 2003; Walker et al, 2010), and may provide insight into the male predominance of certain neurodevelopmental morbidities linked to maternal obesity (autism spectrum disorders, developmental/cognitive delay, ADHD, and in some studies schizophrenia) (Bilbo et al, 2012; Lenz and McCarthy 2015; Edlow 2017a; Koyama and Ikegaya 2015). Recent studies have demonstrated that the placenta may transmit sex‐specific signals to the developing fetal brain in the setting of maternal environmental perturbations, and that such signaling may be mediated in part via X‐linked gene‐dosage effects and sex differences in placental inflammation (Bale 2016; Howerton et al 2013; Bronson and Bale 2014).…”
Section: Discussionsupporting
confidence: 89%
“…The examination of both male and female fetal brains and placentas allowed us to investigate sex differences in response to immune challenge in the setting of maternal obesity. The finding that male brain and placental macrophages have a significantly increased response to LPS in maternal obesity is consistent with other studies that have demonstrated increased male brain vulnerability to early‐life immune challenge (Schwarz et al, 2012; Iwasa et al 2010; Llorente et al 2009; Rebuli et al 2016; Ruggiero et al 2018; Hilton et al, 2003; Nunez et al, 2003; Walker et al, 2010), and may provide insight into the male predominance of certain neurodevelopmental morbidities linked to maternal obesity (autism spectrum disorders, developmental/cognitive delay, ADHD, and in some studies schizophrenia) (Bilbo et al, 2012; Lenz and McCarthy 2015; Edlow 2017a; Koyama and Ikegaya 2015). Recent studies have demonstrated that the placenta may transmit sex‐specific signals to the developing fetal brain in the setting of maternal environmental perturbations, and that such signaling may be mediated in part via X‐linked gene‐dosage effects and sex differences in placental inflammation (Bale 2016; Howerton et al 2013; Bronson and Bale 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Two studies identified contradictory results regarding sex differences in the microglial responses to early alcohol exposure. There is evidence of a female-specific increase in the number of HIP microglial cells in young (P5) rats acutely exposed to ethanol [86]. However, in mice, alcohol exposure had the same effects on microglia in both sexes [88].…”
Section: Postnatal Environmental Agents and Infectionmentioning
confidence: 97%
“…A large body of literature focusing on alcohol exposure in early postnatal life describes an increase in microglial activation markers and phenotype changes in the cortical and subcortical regions of the brain immediately after treatment [77][78][79][80][81][82][83][84][85][86]. Regarding cell density, contrasting findings have been collected, with some studies showing an increase [78,86] and others a decrease [79,85,87] in the number of microglial cells in both cortical and subcortical compartments. It has also been shown that alcohol induces an increase in amoeboid microglia along with a decrease in resting microglia in the HIP and cerebellum [82].…”
Section: Postnatal Environmental Agents and Infectionmentioning
confidence: 99%
“…We did not manipulate hormonal status during sex-specific perinatal organization of the brain, or the activational effects of hormones in later development, so the potential role of hormones in the sex differences reported here is unknown. Across many studies of male and female rodents, prenatal ethanol affects males and females differently (e.g., [74][75][76][77][78][79]). The pattern of our results is quite similar to those of Rodriguez et al [80].…”
Section: Discussionmentioning
confidence: 99%